REVIEW: POTENTIAL PHARMACOLOGICAL ACTIVITY OF KALANGKALA PLANT (Litsea angulata) - Enti Rikomah, Setya; Mahfudh, Nurkhasanah; Yuliani, Sapto (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Kalangkala plants are native to Kalimantan and belong to the genus Litsea, family Lauraceae. Traditionally, it is used to treat diarrhea, boils, dyspepsia, diabetes, pain, asthma, fever, arthritis, traumatic injuries, gastroenteritis, edema, and stomachaches. This review article aims to explain the phytochemical components and pharmacological activities of the kalangkala plant. Databases from Google Scholar, ScienceDirect, and PubMed were searched for articles published from 2016 to 2024. The keywords used were Kalangkala, Litsea, and Litsea angulata. The results showed that Litsea angulata contains phytochemical compounds including saponins, alkaloids, flavonoids, tannins, steroids, triterpenoids, terpenoids, carotenoids, coumarin, ?-pinene, (S)-cis-verbenol and ?-sitosterol. The pharmacological activity of Litsea angulata includes antioxidant, antibacterial, antidiabetic, and spermacidal activities and is toxic. Antioxidant activity of kalangkala plant from various parts of the plant, namely branches, bark, leaves, seeds, fruits, leaves, and fruit seeds. Antibacterial activity in plant parts, namely branches, bark, leaves, seeds, and essential oils from leaves, and antidiabetic activity in the fruit seeds of the kalangkala plant. Litsea angulata is the most widely reported phytochemical component for its pharmacological activity, namely flavonoids. Flavonoids are found in various parts of plants, including the seeds, bark, and leaves. Pharmacological activity as an antioxidant, antibacterial, and antidiabetic. Further research is needed to identify the phytochemical components responsible for the pharmacological activity in the discovery of new drugs. Keywords: Kalangkala, Litsea, Litsea angulata